(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
Due to unequal power relations in the workplace, the centrality of collective bargaining cannot be over-emphasised. Collective bargaining is the central component of industrial relations; it provides mutual understanding and partnership in the workplace. A thriving economy has kept Botswana stable, but collective bargaining has not been as successful. Although trade unions have the freedom to organize, Botswana lacks knowledge and experience in collective bargaining, and the platform of collective bargaining has not been utilized effectively (Tshukudu, 2022). The country institutionalised collective bargaining in 2008, and its track record has been unsatisfactory. The study used exploratory research design to explore collective bargaining in the public sector in Botswana. The study used fifteen participants that were selected from the public service. The findings of the study demonstrate that collective bargaining is still new in Botswana, hence bargaining parties lack capacity in terms of proper and full implementation of collective bargaining. The study recommends capacity building for social partners. Training of bargaining parties on collective bargaining needs to be prioritised. The study also notes that for full development of collective bargaining, bargaining parties should avoid politicisation of collective bargaining.